Improving the Ability of Using Krama Variant of the Javanese Language through Role Play - Praptanti, Isnaeni (EDUCARE, 2010)
ABSTRACT: This research is aimed at knowing whether or not role play is effective in improving studentsâ ability in speaking with âkramaâ variant in Javanese language. This is developmental research taking the eighth-year students of SMP Negeri (State Junior High School) 2 in Purwokerto, Central Java, Indonesia, of the academic year of 2006/2007 as the sample. This research was done in two cycles in CAR (Classroom Action Research), each of which consisted of planning, acting, observing, and reflecting. Each acting stage took 2 x 40 minutes. The data was collected using test, observation, interview, and journal in each cycle. The data was analyzed quantitatively and qualitatively. The initial mean score of studentsâ ability of using âkramaâ variant in Javanese language was 64.5. After the first cycle, it became 67.42 which was categorized as fair. After the second, it was 73 and categorized as good, above the Minimum Competence Criterion. It can therefore be concluded that role play can improve the ability in using âkramaâ variant of the Javanese language of students of SMP Negeri 2 Purwokerto. Process increase can be seen from studentsâ skill in implementing the steps of role play to improve the ability of speaking which is increasing, while productivity improvement can be seen from the grade of role play.KEY WORDS: Role play, âkramaâ variant in Javanese language, CAR (Classroom Action Research), and improving the ability.About the Author: Isnaeni Praptanti, M.Pd. is a Lecturer at the Faculty of Education and Teacher Training UMP (Muhammadiyah University of Purwokerto), Jalan Raya Dukuhwaluh, Purwokerto, Central Java, Indonesia. She can be reached at: tukiranump@yahoo.comHow to cite this article? Praptanti, Isnaeni. (2010). âImproving the Ability of Using Krama Variant of the Javanese Language through Role Playâ in EDUCARE: International Journal for Educational Studies, Vol.3(1) August, pp.55-68. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 22, 2010); Revised (July 22, 2010); and Published (August 17, 2010).